Composation of Polyaluminum Chloride with Hydroxyapatite and Its Application for Separation of Hexavalent Chromium Ions - Basril Simbarta Tarigan; Rukiah Rukiah; Atiek Rostika Noviyanti (Jurnal Keramik dan Gelas Indonesia, 2021)
Chromium  is  the  dominant  heavy  metal  in  liquid waste from the leather tanning industry, wood preservation   and   textile   processing. Generally chromium    waste   is   found   as   trivalent   and hexavalent chromium ions. Hexavalent chromium ion is dangerous  for  humans  because  of  its  carcinogenic  nature, which  can  lead  to  skin  irritation,  lung  cancer,  kidney  and stomach disorders. Coagulation-flocculation (CF) is  a method used to reduce hexavalent chromium ion levels. Polialuminum chloride (PAC) has been widely used in water treatm ent using the  CF  method.  Unfortunately,  however,  the  PAC stability  is poor, the coagulation efficiency  is  low, and the floc formation time is slow. In addition, PAC can produce Al3+ which is toxic in processed water. But its  toxicity  can be overcome by adding donor   ligands   that   contain   oxygen   such   as   hydroxides, carboxylic acids and phosphates, such as hydroxyapatite (HA). In  addition,  the addition of HA with the optimum  composition and pH at PAC can increase the performance of PAC. This study aims to optimize the PAC/HA combination at various pH so as to reduce the concentration of hexavalent chromium ion, controlled by UV-VIS spectroscopy. The highest reduction in Cr (VI) ion content was obtained by PAC, but the highest stability was obtained by the composition of PAC/HA 4: 6.